The Challenge Of Learning Statistical Literacy In Higher Education: A Systematic Literature Review - Habibie, Zulqoidi R.; Kartono; Wardono; Kharisudin, Iqbal (Hipotenusa: Journal of Mathematical Society, 2025)
This study aims to look deeper into the definition of statistical literacy (SL) and learning challenges to improve SL, as SL has become essential for students to face the era of data disruption and quantitative information. Previous research has investigated the level of elementary to high school students. Not many still discuss the definition of SL in students in higher education and what challenges teachers need to prepare for in improving SL. The research questions of this study are as follows: 1) What is the distribution of SL definitions often used in higher education? 2) What challenges will be faced in improving SL? This study was a systematic review of 10 articles with inclusion criteria. The article search was assisted by Publish Or Perish (PoP) software by entering the keyword "SL" in the "title words" in the Scopus search and specifying the year “2018-2023”. The results of this study found that 1) The ability to comprehend, interpret, evaluate critically, communicate, describe, organize, generalize, hypothesize, and visualize statistical data and information is frequently emphasized as constituting SL.; 2) The challenge in improving SL is that educators can develop learning models with a contextual approach and the development of evaluation tools with a contextual approach. In future research, the author suggests that research can be conducted to develop learning models that can improve SL at the college level based on a contextual approach.